Implementation of Differentiated Learning Methods in Increasing Student Learning Motivation at SMPN 23 Surakarta - Natsya Alvia Putranti; Muh. Nur Rochim Maksum (South Sulawesi Education Development (SSED), 2024)
This study investigates the application of differentiated learning methods to boost student motivation in Islamic religious education at SMPN 23 Surakarta. Utilizing a qualitative approach, it examines the implementation process and its impact, highlighting strategies such as mapping learning needs, creating tailored learning plans across four aspects (content, process, product, and environment), and conducting reflective evaluations. This research shows the implementation of differentiated learning methods at SMPN 23 Surakarta in Islamic religious education subjects: 1) Mapping learning needs based on learning readiness, interests, and learning profiles. 2) Make a differentiated learning plan using four aspects (content, process, product, and environment). 3) Carry out differentiated learning by the learning implementation plan that has been made. 4) Reflect and evaluate after the learning process. The impact of differentiated learning methods in increasing student learning motivation at SMPN 23 Surakarta has a positive effect on students; students become more enthusiastic and motivated to participate in Islamic religious education learning activities.